Evaluation of dried blood spot sampling following cassette dosing in drug discovery. (October 2011) - Liang, Xiaorong; Yang, Lulu; Berezhkovskiy, Leonid; Liederer, Bianca; Nguyen, Trung; Jia, Wei; Schweiger, Michelle; Dean, Brian; Deng, Yuzhong
Background: Dried blood spot (DBS) sampling has received growing interest mainly in regulatory preclinical and clinical studies while not routinely used in exploratory discovery pharmacokinetic screening. An intravenous bolus cassette dose of six compounds in rats followed by hemolyzed blood sample (HBS) and DBS sampling was evaluated in this study.Results: A sensitive liquid chromatography tandem mass spectrometry method was developed and qualified for the simultaneous determination of six compounds in rat whole blood using DBS or HBS techniques. The concentrations obtained from DBS samples matched well with those from HBS for each individual compound.Conclusion: This study demonstrated the applicability of DBS sampling for cassette dosing in discovery pharmacokinetics screening.